Conviviality in Burgaz Living, Loving and Fighting on a Diverse Island of Istanbul - Duru, Deniz N. (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
"This insightful ethnography provides a captivating exploration of Burgaz Island where different classes and ethno-religious groups live together. Through the concept of "conviviality," Dr Duru reveals the dynamic social interactions that shape the island's way of life and the islanders' collective identity. This book offers valuable insights for scholars, students, policymakers, and anyone interested in understanding the potential for shared lives across diverse communities." -Elif S. Uyar, Department of Sociology, Çanakkale Onsekiz Mart University, Turkey This open access book tells stories of conviviality, solidarity, and everyday management of conflicts and tensions, by building on original, long-term ethnographic research (fourteen months in 2009-2010, followed by fieldwork trips until now) on Burgaz, an island home to more than twenty ethnic and religious groups from different socio-economic backgrounds. The island provides an excellent case study of post-Ottoman conviviality, as the homogenisation process during the nation-building stage of modern Turkey triggered migrations from the island, especially of non-Muslims, yet the island's population retains elements of its Byzantine and Ottoman diversity. The book explores the islanders' representation of diversity through ethnographic research, media analysis and interviews, and shifts the analytical framework of Post-Ottoman plurality from "coexistence/toleration" to that of conviviality. The author critically engages with the literature on multiculturalism and cosmopolitanism and conceptualises conviviality as both living together in diversity as shared ways of living as well as living with difference. The book further explores the relationship between conviviality, solidarity, coexistence/toleration, intoleration and nationalism.